An ultrasonic piezoelectric motor utilizing axial-torsional coupling in a pretwisted non-circular cross-sectioned prismatic beam - Wajchman, David (IEEE transactions on ultrasonics, ferroelectrics, and frequency control, 2008)
A rotary piezoelectric motor design with simple structural components and the potential for miniaturization using a pretwisted beam stator is demonstrated in this paper. The beam acts as a vibration converter to transform axial vibration input from a piezoelectric element into combined axial-torsional vibration. The axial vibration of the stator modulates the torsional friction forces transmitted to the rotor. Prototype stators measuring 6.5 x 6.5 x 67.5 mm were constructed using aluminum (2024-T6) twisted beams with rectangular cross-section and multilayer piezoelectric actuators. The stall torque and noload speed attained for a rectangular beam with an aspect ratio of 1.44 and pretwist helix angle of 17.7 degrees C were 0.17 mNm and 840 rpm with inputs of 184.4 kHz and 149 mW, respectively. Operation in both clockwise and counterclockwise directions was obtained by choosing either 70.37 or 184.4 kHz for the operating frequency. The effects of rotor preload and power input on motor performance were investigated experimentally. The results suggest that motor efficiency is higher at low power input, and that efficiency increases with preload to a maximum beyond which it begins to drop